Altered Brain Structure and Spontaneous Functional Activity in Children With Concomitant Strabismus - Yin, Xiaohui; Chen, Lingjun; Ma, Mingyue; Zhang, Hong; Gao, Ming; Wu, Xiaoping; Li, Yongqiang (Frontiers in Human Neuroscience, 2021)
Strabismus occurs in about 2% of children and may result in amblyopia or lazy eyes and loss of depth perception. However, whether/how long-term strabismus shapes the brain structure and functions in children with concomitant strabismus (CS) is still unclear. In this study, a total of 26 patients with CS and 28 age-, sex-, and education-matched healthy controls (HCs) underwent structural and resting-state functional magnetic resonance imaging examination. The cortical thickness and amplitude of low-frequency fluctuation (ALFF) were calculated to assess the structural and functional plasticity in children with CS. Compared with HCs group, patients with CS showed increased cortical thickness in the precentral gyrus and angular gyrus while decreased cortical thickness in the left intraparietal sulcus, parieto-occipital sulcus, superior and middle temporal gyrus, right ventral premotor cortex, anterior insula, orbitofrontal cortex, and paracentral lobule. Meanwhile, CS patients exhibited increased ALFF in the prefrontal cortex and superior temporal gyrus, and decreased ALFF in the caudate and hippocampus. These results show that children with CS have abnormal structure and function in brain regions subserving eye movement, controls, and high-order cognitive functions. Our findings revealed the structural and functional abnormalities induced by CS and may provide new insight into the underlying neural mechanisms for CS.